Substituto processual: limites subjetivos da coisa julgada em relação ao substituído diante das garantias constitucionais do acesso à justiça e do contraditório - Silva, Nelson Finotti (2008)
Since the 1988 Constitution, Brazilian procedural system has suffered deep changes with the inclusion of principles and procedural warranties within it. These did not exist before and provoke effects into all civil procedural jural order. The principles and constitutional warranties are the basis of the procedural system, remanding the right operator to investigate and reread the procedural rules from National Constitution. The Constitution is embodied in a historical period and cannot be separated from this time concrete reality. The principles and the warranties point the direction and whatever the rule supported by them is not supposed to contradict the imposed North; thus, the interpreter has no right to any conclusion that might vitiate all constitutional structure. It is undisputed that the1988 Constitution has brought a new conception of State and the values assured by it. Specifically concerning the civil procedure, the procedural system, as mentioned before, supported by constitutional fundamental principles and imposing a jural political order as a whole, has been maintained upon four bases: the jurisdiction, the action, the defense and the proceeding. These constitute the normative constitutional structure and the present work seeks to, through examining the constitutional principles and warranties of the access to justice and adversary, reevaluate the institute of procedural substitute and the res judicata in the presence of constitutional normative force of mentioned principles and warranties